ACUTE TISSUE EXPANSION FOR RECONSTRUCTION OF MAJOR DEFECTS OF THE FRONTAL REGION - David Pacheco; Ermelindo Tavares; José Rosa de Almeida (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Acute tissue expansion is a procedure widely used by Plastic Surgery for the closure of large surgical defects located in the head and the neck. We present a 61-year-old patient, with a large dimension Dermatofibrosarcoma protuberans of 45x30mm, placed in the midline of the forehead. The expected surgical defect was considerable; this combined with the anatomical situation, involved a complex reconstructive surgery, which would be resolved with the creation of a flap. Acute tissue expansion is a simple technique that can be performed in a unique surgical procedure, with good cosmetic outcome, minimizing technical difficulties and complications of invasive procedures.